Алгебро-алгоритмічні засоби побудови клітинкових автоматів та застосування їх до розв'язку початково-крайових задач. - Захарія, Любов; Захарія, Олег (Видавництво Національного університету «Львівська політехніка», 2009)
This work deals with the cellular automaton that was build using algebra-algorithmic facilities for solving linear boundary problems. As an example was taken "prey-predator" model which describes correlation of predators and victims populations. Obtained results was compared to solutions of Lotka-Voltera model, that is corresponding to "prey-predator" model, that have been received by using mathematical methods.
Keywords: cellular automaton; prey-predator model; algebra-algorithmic facilities